2006
DOI: 10.1016/j.seppur.2005.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Temperature swing adsorption of heavy metals on novel phosphate-type adsorbents using thermosensitive gels and/or polymers

Abstract: A novel thermosensitive adsorbent was developed, which adsorbs and/or desorbs heavy metals through temperature swing process. The gel-type and polymer-type adsorbents, composed of N-isopropylacrylamide (NIPA) as a thermosensitive component and 2-methacryloyloxyethyl phosphate (MEP) as an interactive component, were prepared by free radical copolymerization. For each type of poly(NIPA-co-MEP), phase transitions and temperature dependences for the amount of Cu, a model metal ion, adsorbed was examined. The propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 12 publications
(18 reference statements)
0
32
0
Order By: Relevance
“…1 The unique properties of PNIPAM inspired researchers to combine PNIPAM with polystyrene (PS) in areas such as biomedical 2 and bioseparations, 3 drug delivery, 4 catalysts, 5 and pollution control. 6 However, it is interesting to note that almost all of the research reported in the literature focused on synthesizing a PNIPAM shell around a PS core (or similar other polymeric materials), [7][8][9][10] although there are several studies describing the synthesis of a PNIPAM-based core and a PS shell. 11,12 It is thermodynamically favorable to form a hydrophilic shell around a hydrophobic core.…”
Section: Introductionmentioning
confidence: 99%
“…1 The unique properties of PNIPAM inspired researchers to combine PNIPAM with polystyrene (PS) in areas such as biomedical 2 and bioseparations, 3 drug delivery, 4 catalysts, 5 and pollution control. 6 However, it is interesting to note that almost all of the research reported in the literature focused on synthesizing a PNIPAM shell around a PS core (or similar other polymeric materials), [7][8][9][10] although there are several studies describing the synthesis of a PNIPAM-based core and a PS shell. 11,12 It is thermodynamically favorable to form a hydrophilic shell around a hydrophobic core.…”
Section: Introductionmentioning
confidence: 99%
“…Several articles showed that others versatile functionalities are sulfonate groups and phosphoric groups. [68,69] . They were able to create thermosensitive resins with LCST able to bind Cu (II) ions; finally thiacrown polymers immobilized on polystyrenedivinylbenzene were employed for Hg (II) removal [70] .…”
Section: Polymers For Heavy Metals Removalmentioning
confidence: 99%
“…For example, the adsorption amount with PNIPAAm-VBEDA ranged from 0.001 to 0.012 mmol/gdrygel, 12 and that of PNIPAAm-MEP ranged from 0.015 to 0.035 mmol/g-drygel. 25 The magnificent increase of adsorption should ascribe to the nanoscale particle size. The PNIPAAm-MAA particle size ranged from 30 to 500 nm, which greatly increased the effective contact area of the MAA and Cu 21 ions.…”
Section: Cu 21 Ion Adsorption From Cuso 4 Solutionmentioning
confidence: 99%